Sistem Informasi Geografis Pemetaan Jumlah Pengangguran 2020-2022 Serta Lowongan Kerja di Kabupaten-Kabupaten Jawa Tengah 2018,2020,2021 - Reza aditya pratama; Bambang agus herlambang; Khoirul anam (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Geographic Information Systems (GIS) have become a very effective tool in supporting various fields, including mapping the number of unemployed and job vacancies for the community. This research aims to provide information so that equality can occur in Central Java and as a means for the community to obtain information about areas that have more job vacancies. This research method involves collecting spatial and attribute data from areas involved in the Desa Siaga program. Data on the number of unemployed and job vacancies are taken from data from the Central Statistics Agency. GIS technology is used to map the distribution of the number of unemployed in districts and analyze the correlation with job vacancies in each region of Central Java.